2010
DOI: 10.1111/j.1399-3038.2009.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental anxiety before and after food challenges in children with suspected peanut and hazelnut allergy

Abstract: As ingestion of peanut and hazelnut by allergic children is potentially life threatening, parents of these children need to be vigilant about their child's dietary intake. This may cause high levels of anxiety. To assess parental anxiety about food-allergic reaction in their child (state anxiety) and their personal disposition to anxiety (trait anxiety). Parental anxiety was investigated again after food challenges. Fifty-seven children (3-16 yr, mean age 7.2) with suspected peanut or hazelnut allergy (mean sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…This was also shown recently for food challenges in children in a study where a decrease in parental anxiety was documented even in the group with a positive test result [15]. …”
Section: Discussionmentioning
confidence: 84%
“…This was also shown recently for food challenges in children in a study where a decrease in parental anxiety was documented even in the group with a positive test result [15]. …”
Section: Discussionmentioning
confidence: 84%
“…Overall, our findings are in agreement with those of previous literature, which showed that parent-proxy reports on the child's HRQL improved significantly after a food challenge in children aged 0 to 12 years and that larger improvements in HRQL were shown after a negative outcome than after a positive outcome. 3 Additionally, other studies on parents' perceptions of their child's food challenge [23][24][25][26] showed reduced parental concerns 25,26 and parental anxiety 24 after food challenges, irrespective of the outcome of the challenge. It was hypothesized that these improvements in HRQL/well-being were caused by the fact that a definitive diagnosis provides a sense of certainty.…”
Section: Discussionmentioning
confidence: 97%
“…A cutoff point of a probability of > _0. 6 showed the best diagnostic accuracy with regard to the PPV and the NPV (93% and 83%, respectively; Table III).…”
Section: Phase 2: Updating the Prediction Model With Additional Predimentioning
confidence: 92%
“…[1][2][3] It has an important influence on daily life for both children and their parents, especially because of the strict elimination diet that is generally prescribed. [4][5][6] The gold standard to diagnose a peanut allergy is a doubleblind, placebo-controlled food challenge (DBPCFC). 7 This is a costly and, especially for young children, burdensome test demanding specialized medical facilities.…”
mentioning
confidence: 99%